Class Rank and Long-Run Outcomes - Jeffrey T. Denning; Richard J. Murphy; Felix Weinhardt (Institute of Labor Economics (IZA), 2018)
This paper considers a fundamental question about the school environment – what are the long run effects of a student's ordinal rank in elementary school? Using administrative data from all public school students in Texas, we show that students with a higher third grade academic rank, conditional on ability and classroom effects, have higher subsequent test scores, are more likely to take AP classes, graduate high school, enroll in college, and ultimately have higher earnings 19 years later. Given these findings, the paper concludes by exploring the tradeoff between higher quality schools and higher rank.
Keywords: I20; I23; I28; 330; rank; education; subject choice